Exploring staff experience of an "enriched environment" within stroke rehabilitation: a qualitative sub-study. (October 2014) - White, Jennifer H.; Alborough, Katherine; Janssen, Heidi; Spratt, Neil; Jordan, Louise; Pollack, Michael
Abstract Background: Environmental Enrichment (EE) is shown to facilitate recovery of motor and cognitive function in animal models of stroke. The efficacy of EE in the clinical setting with stroke survivors remains unknown. Successful implementation of EE in a busy rehabilitation unit requires identification of barriers and enablers which are best informed by staff feedback. Aim: To qualitatively explore the experiences of nursing staff involved in a pilot study investigating the feasibility of EE in a rehabilitation ward. Methods: This was a qualitative study consisting of analysis of semi-structured interviews with nine nursing staff who were asked to reflect on "routine care" and their own "experience of the EE study". An inductive thematic approach was used to collect and analyse data using a process of constant comparison. Results: Male and female staff with varying years of experience working in stroke rehabilitation participated in focus group and individual interviews. Three key themes were identified concerning the implementation of EE including: (i) "Nurses are so busy" – perceptions on routine work practice; (ii) "A better outlook" – perceptions of the benefit of EE; (iii) "They're just not going to participate" – perceptions of barriers to EE. Indeed, the challenges identified in this study align with practice change literature, which indicates that staff workload, routine and attitudes can influence the implementation of a new practice. Discussion: Staff perceived the use of an EE in their rehabilitation unit promoted activity/participation and increased patient moral. The barriers and enablers experienced by staff in this study may be used to inform the design and conduct of future studies investigating the efficacy of EE during inpatient stroke rehabilitation after stroke. Implications for Rehabilitation Results from animals models suggest that environmental enrichment (EE) is an important paradigm for consideration in stroke rehabilitation. It is concerning that many stroke survivors are inactive during their admission for inpatient stroke rehabilitation. Preliminary results suggest that rehabilitation nurses perceive that EE promoted patient activity/participation. Results highlight the importance of social support and participation in the ward environment and potential benefits for patient's mood levels.